Longevity and development of Aedes aegypti larvae to imago in domestic sewage water - M Martini; Yuniar Triasputri; Retno Hestiningsih; Sri Yuliawati; Susiana Purwantisasi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Dengue Hemorrhagic Fever (DHF) caused by dengue virus transmitted by Aedes aegypti (Ae. Aegypti) that lives and breeds in clean water. The aim of the study was to analyze the difference of the longevity and development of Ae. aegypti larva in the difference pH of domestic sewage water. This experimental used post only control group design to analyze population of Ae. aegypti instar III larvae which was bred in the Entomology Laboratory of the Faculty of Public Health, Diponegoro University, Semarang, Central Java. The number of tested larvae was 25 per media with six replications. Thus, the total number of larvae was 750. Data were analyzed using Kruskal Wallis and followed by Mann Whitney test. The result showed that Ae. aegypti larva could survive and breed to be mosquitos in the domestic sewage water with various pH levels. There was significant difference between the number of larvae transforming to pupa (p=0.002), pupa to imago (p=0.001), and the number of survival imago until second week (p<0.001) in the domestic waste water with various pH levels. Other findings revealed that people tended to wash away larvae they found in the water, but still used the water for daily live. As a result, the larvae bred in the domestic sewage water. Therefore, elimination breeding place (EBP) program needs to be socialized to make people aware of either domestic waste water or domestic clean water.